2018
DOI: 10.3389/fcell.2018.00060
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Protein O-GlcNAcylation During Mouse Epididymal Sperm Maturation

Abstract: After leaving the testis, sperm undergo two sequential maturational processes before acquiring fertilizing capacity: sperm maturation in the male epididymis, and sperm capacitation in the female reproductive tract. During their transit through the epididymis, sperm experience several maturational changes; the acquisition of motility is one of them. The molecular basis of the regulation of this process is still not fully understood. Sperm are both transcriptionally and translationally silent, therefore post-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 48 publications
2
17
0
1
Order By: Relevance
“…Several posttranslational modifications (PTMs), such as phosphorylation, glycosylation (Baker 2016) and O-GlcNAcylation (Tourzani et al 2018) of sperm proteins occur during epididymal sperm maturation. The importance of the PTMs is still unclear, but as sperm are transcriptionally silent cells, PTMs provide a means of controlling the protein activity in sperm.…”
Section: Epididymal Proteins Modifying Sperm Proteinsmentioning
confidence: 99%
“…Several posttranslational modifications (PTMs), such as phosphorylation, glycosylation (Baker 2016) and O-GlcNAcylation (Tourzani et al 2018) of sperm proteins occur during epididymal sperm maturation. The importance of the PTMs is still unclear, but as sperm are transcriptionally silent cells, PTMs provide a means of controlling the protein activity in sperm.…”
Section: Epididymal Proteins Modifying Sperm Proteinsmentioning
confidence: 99%
“…de la activación de la vía AMPc/PKA. Por el contrario, el cambio en el patrón de motilidad a un estado hiperactivado, es completamente dependiente de la producción temprana de AMPc por sAC y consecuente activación de PKA (Tourzani et al, 2018).…”
Section: El Desanclaje De Pka Inhibe El Movimiento Hiperactivadounclassified
“…Capacitation is associated with the activation of several signaling pathways including but not limited to an increase in cAMP levels with the consequent activation of a protein phosphorylation cascade. Importantly, in immature sperm, phosphorylation is impaired even in the presence of exogenous permeable cAMP analogues [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, epididymal maturation is associated with inactivation of the serine/threonine protein phosphatase 1 gamma Ppp1cc (also known as PP1γ2) [ 20 , 21 ]. More recently, our group has shown that protein O-GlcNAcylation changes in sperm during epididymal maturation [ 12 ]. Immature caput sperm exhibited high O-Linked β-N-Acetylglucosamine (O-GlcNAc) Transferase (OGT) protein levels corresponding with high levels of protein O-GlcNAcylation while mature cauda sperm exhibited levels of OGT and O-GlcNAcylation significantly lower [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation